Magnetic resonance imaging guided focused ultrasound in thw treatment of neurological disorders - Antoniou, Anastasia (My University, 2023)
Magnetic Resonance guided Focused Ultrasound (MRgFUS) has emerged in the field of neurosurgery as a non-invasive modality for the treatment of various brain diseases. Numerous studies involving the use of mouse models have shown that extracorporeal FUS administered with an US contrast agent can transiently disrupt the Blood Brain Barrier (BBB) so that molecules of pharmacologically relevant size can enter the brain parenchyma to impart therapeutic effects. This doctoral study aimed to provide insights on the topic of transcranial FUS (tFUS) through a series of ex-vivo and in-vivo preclinical experiments. Realistic phantom models were developed to mimic all the critical properties of live tissue and assessed for their feasibility as quality assurance tools for tFUS procedures. The developed tissue mimicking phantoms served as the main tool for evaluating the practicality of using single-element ultrasonic transducers in trans-skull thermal applications. Critical topics of the preclinical assessment of newly developed systems and emerging applications in the context of MRgFUS were also covered. The study further presents the development of a compact single-stage positioning device dedicated to tFUS applications in small animal models, which was evaluated for its ability to cause safe and efficient BBB disruption (BBBD) in Wild Type mice. The next key objective was to examine the capability of specific anti-Aβ antibodies to penetrate the brain tissue following FUS-mediated BBBD and impart therapeutic effects in the 5XFAD mouse model of the Alzheimer's disease (AD), thus potentially holding promise for the development of disease-modifying therapeutics for AD patients. Some preliminary outcomes on the potential feasibility of this technology in the treatment of neurodevelopmental disorders are reported as well.
Keywords: MRgFUS; brain; transcranial; mice; tissue mimicking phantoms